THE INFLUENCE OF THE UNITED STATES CAATSA POLICY ON INDONESIAN DEFENSE DIPLOMACY - Jayadi, Usman; Hersa Putra Pratama, M. Reynaldo (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2023)
Indonesia almost finished purchasing Su-35 fighter jets that were made by Russia in 2018. But, the purchase was canceled because of the shadow of coercive diplomacy from the United States's CAATSA. Indonesia chose to obey CAATSA by canceling purchasing Russian fighter jets and changing it by purchasing Dassault Rafale fighter jets made by France. This research aims to see what Indonesia would do to its defense development. The answer will be found through the concept of defense diplomacy and descriptive-analytical methods. This research shows that the implementation of Indonesian defense diplomacy aims to build Confidence Building Measures by increasing defense cooperation with other countries and creating independence in the arms sector by Transfer of Technology to Indonesian defense industry.